2013
DOI: 10.1037/a0034693
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and parenting in ethnic minority families: Testing a minority family stress model.

Abstract: According to the family stress model (Conger & Donnellan, 2007), low socioeconomic status (SES) predicts less-than-optimal parenting through family stress. Minority families generally come from lower SES backgrounds than majority families, and may experience additional stressors associated with their minority status, such as acculturation stress. The primary goal of this study was to test a minority family stress model with a general family stress pathway, as well as a pathway specific to ethnic minority famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 56 publications
(113 reference statements)
6
69
0
1
Order By: Relevance
“…Problems in these three areas are associated with poor parental functioning, which in turn is linked to poor child and family outcomes. In support of this model, past research has found that maternal depression, difficult child temperament, child behavior problems, low social support, and limited financial resources are linked to high levels of parenting stress and harsh parenting practices [26,8,12,15]. Relatively less research has examined how maternal physical health influences parenting stress, especially in contexts where mothers are struggling to raise high-risk children with limited financial and social resources.…”
Section: Parenting Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Problems in these three areas are associated with poor parental functioning, which in turn is linked to poor child and family outcomes. In support of this model, past research has found that maternal depression, difficult child temperament, child behavior problems, low social support, and limited financial resources are linked to high levels of parenting stress and harsh parenting practices [26,8,12,15]. Relatively less research has examined how maternal physical health influences parenting stress, especially in contexts where mothers are struggling to raise high-risk children with limited financial and social resources.…”
Section: Parenting Stressmentioning
confidence: 99%
“…Mothers of low-socioeconomic status (SES) and who are ethnically or racially diverse are particularly vulnerable to poor physical and mental health [2123] and high parenting stress [46]. This may be due to structural disadvantages such as limited access to quality health care and low social and financial support [2,4,10].…”
Section: Socioeconomic Status and Social Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Acculturation stress may be particularly salient in the development of self-regulation skills for first-generation immigrant families living in low-income households (Li-Grining, 2012). Given that all of the mothers in our sample were low income and the majority were first-generation immigrants and spoke Spanish only, it is likely that they faced some level of discrimination and acculturation stress (Emmen et al, 2013; Schwartz et al, 2010). However, at this stage of the study, we did not include measurement of such stress, and we were therefore unable to examine how it impacted parenting and child outcomes presented here.…”
Section: Discussionmentioning
confidence: 99%